1997
DOI: 10.1002/(sici)1097-0185(199707)248:3<421::aid-ar15>3.3.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in the myocardial architecture of the chick

Abstract: Background: Numerous studies describing myocardial architecture have been performed on the adult heart but considerably fewer have been made during embryonic or fetal development. To serve as a basis for interspecies comparison of ventricular morphology, and as a reference for studying the effects of experimental perturbations, we examined the development of chick throughout the entire incubation period.Methods: Chick hearts from stage 14 (day 2) to stage 46 (day 21) were perfusion-fixed, and sectioned in tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The mural/lateral cushions form the mural leaflets. The right mural cushion of the chick becomes muscularized (like the conus region of the OT) forming a large muscular flap, while the right AV septal leaflet is only a 'micro-leaflet' (Sedmera et al 1997). The right AV valves in the mouse, however, are similar in structure and morphogenesis to the tricuspid valve of the human (Wessels & Sedmera 2003).…”
Section: (I) Atrioventricular Valvesmentioning
confidence: 99%
“…The mural/lateral cushions form the mural leaflets. The right mural cushion of the chick becomes muscularized (like the conus region of the OT) forming a large muscular flap, while the right AV septal leaflet is only a 'micro-leaflet' (Sedmera et al 1997). The right AV valves in the mouse, however, are similar in structure and morphogenesis to the tricuspid valve of the human (Wessels & Sedmera 2003).…”
Section: (I) Atrioventricular Valvesmentioning
confidence: 99%
“…A small number of cells in AV and SL valves are not derived from endothelial or neural crest cells. In avians, but not mammals, one leaflet of the tricuspid valve is highly muscularized, suggesting some contribution from myocardial cells (Lincoln et al, 2004;Sedmera et al, 1997). In line with this, a lineage tracing study using a cardiomyocyte-specific Tnnt2Cre in mice revealed that a small number of myocardial Isl1 + cells also contribute to the SL valves.…”
Section: Embryonic Sources Of Cardiac Valve Cellsmentioning
confidence: 77%
“…Meanwhile, by the end of week 4 in human gestation, the primitive ventricle starts developing trabecular structures, which resemble a sponge-like porous structure [25,26]. These trabecular structures aid ventricular contraction, and their architecture is influenced by blood flow conditions [26 -29].…”
Section: Embryonic Cardiovascular Developmentmentioning
confidence: 99%